Increasing experience in the use of papaya for burn injuries in an African context, potential and limitations - Helena W.C. Hofland; Edris W. Kalanzi; Emmie Viyuyi; Tilinde Chokotho; Titus M. Opegu; Eduard E. Zijlstra (Burns Open)
World-wide, burns are most common in low resource settings (LRS) with high mortality. Human resources, equipment and affordable, effective and safe treatments all influence outcome. Treatment of full thickness burns is particularly challenging and associated with high risk of complications. The presence of an eschar, infection and hypergranulation are important factors that delay wound closure. Tropical fruits are used for treatment of wounds and burns with excellent results. These fruits are usually available throughout the year and essentially inexpensive. The efficacy of papaya and pineapple is based on enzymes that have proteolytic activity and other compounds that have antimicrobial action. In the context of reverse technology, this enzymatic therapy has formed the basis of Nexobrid™ (based on enzymes derived from pineapple) that is now standard of care in high income countries. However, it is painful and very expensive. In LRS the use of papaya paste seems an alternative attractive option; however, evidence-based studies are needed on efficacy, safety, including standardization of the product used and treatment regimens.